Nueva Sede de Gas Natural - EMBT (2000)
Barcelona, España 1999. Concurso primer premio
Keywords: MIRALLES, ENRIC; TAGLIABUE, BENEDETTA; ESPAÑA; BARCELONA; CONCURSOS; PREMIOS; EDIFICIOS ADMINISTRATIVOS